Redistribution in a Globalized World - David R. Agrawal; Dirk Foremny (Center for Economic Studies and ifo Institute (CESifo), 2022)
Due to technological change, the opening of borders, and increased economic integration, the financial costs of relocating businesses and factors of production, moving residences, changing jobs, and transporting goods and services across borders pose new challenges for countries and subnational governments seeking to implement redistributive policies. This increasing mobility across borders implies that redistributive policies may amplify interjurisdictional fiscal externalities. In this article, we selectively review the literature relating to redistributive policy in an open economy setting. We then consider some of the implications of globalization for policy design, both within federal systems and across countries. Although globalization poses new challenges for fiscal systems, it does not necessarily imply that redistributive policy becomes untenable and possibly enhances the need for redistribution.
Keywords: H20; H70; F60; 330; globalization; redistributive policy; mobility